2024
DOI: 10.3310/atpr4281
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of quality of life for hospitalised patients with COVID-19: a scoping review

Edward JD Webb,
Natalie King,
Daniel Howdon
et al.

Abstract: Background Information on the quality of life of people hospitalised with COVID-19 is important, both in assessing the burden of disease and the cost-effectiveness of treatments. However, there were potential barriers to collecting such evidence. Objective To review the existing evidence on quality of life for people hospitalised with COVID-19, with a focus on the amount of evidence available and methods used. Design A scoping review with systematic searches. Results A total of 35 papers were selected for d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Quality-of-life data were not collected from patients, so previously published values were used to represent their utility. A review of the literature 13 revealed a paucity of relevant data on quality of life for people hospitalized with COVID-19. Baseline utilities were calculated using the age/sex-specific UK population norms used by McNamara et al ., 14 and in line with previous studies 15 each day in a general ward/ICU was assigned a utility decrement.…”
Section: Methodsmentioning
confidence: 99%
“…Quality-of-life data were not collected from patients, so previously published values were used to represent their utility. A review of the literature 13 revealed a paucity of relevant data on quality of life for people hospitalized with COVID-19. Baseline utilities were calculated using the age/sex-specific UK population norms used by McNamara et al ., 14 and in line with previous studies 15 each day in a general ward/ICU was assigned a utility decrement.…”
Section: Methodsmentioning
confidence: 99%